Bounds on the Distance Energy and the Distance Estrada Index of Strongly Quotient Graphs - Ş. Burcu Bozkurt; Chandrashekara Adiga; Durmuş Bozkurt (Journal of Applied Mathematics)
The notion of strongly quotient graph (SQG) was introduced by Adiga et al. (2007). In this paper, we obtain some better results for the distance energy and the distance Estrada index of any connected strongly quotient graph (CSQG) as well as some relations between the distance Estrada index and the distance energy. We also present some bounds for the distance energy and the distance Estrada index of CSQG whose diameter does not exceed two. Additionally, we show that our results improve most of the results obtained by Güngör and Bozkurt (2009) and Zaferani (2008).